Valence fluctuations in the 3D + 3 modulated Yb3Co4Ge13 Remeika phase. Issue 38 (13th September 2021) - Feig, Manuel; Akselrud, Lev; Motylenko, Mykhaylo; Bobnar, Matej; Wagler, Jörg; Kvashnina, Kristina O.; Levytskyi, Volodymyr; Rafaja, David; Leithe-Jasper, Andreas; Gumeniuk, Roman
Abstract : Yb3 Co4 Ge13 is the first example of a Remeika phase with a 3D + 3 [space group P 4̄3 n ( α, 0, 0)000(0, α, 0)000(0, 0, α )000; a = 8.72328(1) Å, α = 0.4974(2)] modulated crystal structure. Abstract : Yb3 Co4 Ge13 is the first example of a Remeika phase with a 3 D + 3 [space group P 4̄3 n ( α, 0, 0)000(0, α, 0)000(0, 0, α )000; a = 8.72328(1) Å, α = 0.4974(2)] modulated crystal structure. A slight shift of the composition towards higher Yb-content ( i.e. Yb3.2 Co4 Ge12.8 ) leads to the disappearance of the satellite reflections and stabilization of the disordered primitive cubic [space group Pm 3̄ n, a = 8.74072(2) Å] Remeika prototype structure. The stoichiometric structurally modulated germanide is a metal with hole-like charge carriers, where Yb-ions are in a temperature-dependent intermediate valence state varying from +2.60 to +2.66 for the temperature range 85–293 K. The valence fluctuations have been investigated by means of temperature dependent X-ray absorption spectroscopy, magnetic susceptibility and thermopower measurements.